RANCANG BANGUN AUGMENTED DAN VIRTUAL REALITY MENGGUNAKAN ALGORITMA FAST SEBAGAI MEDIA INFORMASI 3D DI UNIVERSITAS SATYA NEGARA INDONESIA - Faizal Zuli (Universitas Bunda Mulia, 2018)
The role of the media is quite important in providing information to the public about the University of Satya negara Indonesia. Delivery of information is usually done orally and in the form of a two-dimensional such as posters, brochures, as well as through the website. Media such information certainly has its advantages and disadvantages respectively. For it makes the author want to design a media campaign to complement the usual media used by the campus. The making of a media promotion of the technology to implement multimedia computer, namely a merger between Augmented Reality (AR) and Virtual Reality (VR). Augmented Reality and Virtual Reality was selected because of its advantages in describing a building object in 3 dimensions (3D) in real time, to facilitate the user in knowing the information about the campus of the University of Satya negara Indonesia, which can be used on a Smartphone. In the design of inimenerapkan algorithm of FAST Corner Detection as well as using methods of Multimedia Development Life Cycle (MDLC).Keyword : Augmented Reality, Satya Negara Indonesia University, Virtual Reality, 3D